Serology reflects a decline in the prevalence of trachoma in two regions of The Gambia. Issue 1 (December 2017) - Migchelsen, Stephanie; Sepúlveda, Nuno; Martin, Diana; Cooley, Gretchen; Gwyn, Sarah; Pickering, Harry; Joof, Hassan; Makalo, Pateh; Bailey, Robin; Burr, Sarah; Mabey, David; Solomon, Anthony; et al.
Abstract Trachoma is caused byChlamydia trachomatis (Ct). It is targeted for global elimination as a public health problem. In 2014, a population-based cross-sectional study was performed in two previously trachoma-endemic areas of The Gambia. Participants of all ages from Lower River Region (LRR) (N = 1028) and Upper River Region (URR) (N = 840) underwent examination for trachoma and had blood collected for detection of antibodies against the Ct antigen Pgp3, by ELISA. Overall, 30 (1.6%) individuals had active trachoma; the prevalence in children aged 1–9 years was 3.4% (25/742) with no statistically significant difference in prevalence between the regions. There was a significant difference in overall seroprevalence by region: 26.2% in LRR and 17.1% in URR (p < 0.0001). In children 1–9 years old, seroprevalence was 4.4% in LRR and 3.9% in URR. Reversible catalytic models using information on age-specific seroprevalence demonstrated a decrease in the transmission of Ct infection in both regions, possibly reflecting the impact of improved access to water, health and sanitation as well as mass drug administration campaigns. Serological testing for antibodies to Ct antigens is potentially useful for trachoma programmes, but consideration should be given to the co-endemicity of sexually transmitted Ct infections.